Penanaman Budaya Anti Korupsi Dalam Rangka Penanggulangan Korupsi Di Indonesia - Imam Riyadi; Soca Ahmad; Dzikril Hakim; Kalfin Febrian Nababan (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Corruption is like a cancer that eats away at the Indonesian nation, hampering progress and eroding public trust. Efforts to overcome this require a comprehensive approach, one of which is by instilling an anti-corruption culture. This journal examines the importance of instilling an anti-corruption culture as a strategic solution in fighting corruption in Indonesia. This study uses a qualitative method with a descriptive analytical approach. Data was collected through literature studies of books, scientific journals and other trusted sources. An anti-corruption culture is an important foundation for building a dignified and just nation. Efforts to instill this must be carried out systematically and sustainably, Including anti-corruption education in the school and college curriculum. Instilling the values ​​of honesty, integrity and responsibility from an early age in the family. Building an environment that supports an anti-corruption culture through the active role of civil society and organizations social.Instilling an anti-corruption culture is a crucial step in efforts to eradicate corruption in Indonesia. Success requires strong commitment and cooperation from all parties, including the government, educational institutions, families and society.